2020
DOI: 10.1128/jvi.00140-20
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Gamma Interferon-Producing PLZFloRORγtloInvariant Natural Killer 1 Cells Infiltrating Herpes Simplex Virus 1-Infected Corneas Is Associated with Asymptomatic Ocular Herpesvirus Infection

Abstract: Invariant natural killer (iNKT) cells are among the first innate immune cells to elicit early protective immunity that controls invading viral pathogens. The role of the iNKT cell subsets iNKT1, iNKT2, and iNKT17 in herpesvirus immunity remains to be fully elucidated. In this study, we examined the protective role of cornea-resident iNKT cell subsets using the mouse model of ocular herpesvirus infection and disease. Wild-type (WT) C57BL/6 (B6) mice and CD1d knockout (KO) mice were infected ocularly with herpes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…HSV-1 Infection. HSV-1 triggers inflammatory responses, such as gingival stomatitis, cold sores, keratitis, and meningitis [26,27]. To investigate the effect of berberine on inflammatory responses caused by HSV-1, RT-qPCR and ELISA were conducted.…”
Section: Berberine Decreases Inflammatory Responses Induced Bymentioning
confidence: 99%
“…HSV-1 Infection. HSV-1 triggers inflammatory responses, such as gingival stomatitis, cold sores, keratitis, and meningitis [26,27]. To investigate the effect of berberine on inflammatory responses caused by HSV-1, RT-qPCR and ELISA were conducted.…”
Section: Berberine Decreases Inflammatory Responses Induced Bymentioning
confidence: 99%
“…It has recently been shown that in vitro, IFNκ is also secreted by human keratinocytes and blocking IFNκ expression enhances HSV-1 replication, indicating it may also play a role in controlling HSV-1 in herpes lesions [ 140 ]. Secreted type I IFN, among other cytokines, including IL12, IL15, and IL18, activate NK cells, which produce IFNγ, which plays an important protective role against both HSV-1 and HSV-2 infections [ 35 , 141 , 142 ]. CD4+ and CD8+ T cells also infiltrate the dermis contributing to the production of IFNγ [ 143 , 144 , 145 ] ( Figure 2 ).…”
Section: The Interferon Response Against Hsvmentioning
confidence: 99%
“…This has important implications for which NK cell subsets home to particular sites during infection and the kinetics of doing so depending on the cascade of cytokines and chemokines produced over time. In addition to NK cells, decreased IFN-g, IL-6 and IL-12 were observed in symptomatic mice where invariant natural killer T (iNKT) cells were lacking (104). The relative importance of iNKT cells in HSV infection is still poorly understood, although a role for them has been shown in mouse models (104).…”
Section: Natural Killer Cellsmentioning
confidence: 99%
“…In addition to NK cells, decreased IFN-g, IL-6 and IL-12 were observed in symptomatic mice where invariant natural killer T (iNKT) cells were lacking (104). The relative importance of iNKT cells in HSV infection is still poorly understood, although a role for them has been shown in mouse models (104). Therefore the relative roles of NK and iNKT cells in HSV infection should be further explored, partly in human ex vivo model systems.…”
Section: Natural Killer Cellsmentioning
confidence: 99%